An Overview: Recent Development of Titanium Dioxide Loaded Graphene Nanocomposite Film for Solar Application - W. Lai, Chin; W. Low, Foo; W. Chong, Soon; P.P. Wong, Christelle; Binti Mohamed Siddick, Siti Z.; C. Juan, Joon; B. Abdul Hamid, Sharifah (Current Organic Chemistry, 2015)
Recent studies have indicated that graphene is a relatively novel material with unique properties that could apply in solar-based application, such as quantum dot solar cells (QDSSCs), dye-sensitized solar cells (DSSCs), and perovskite solar cell (MSSCs). Graphene film is considered to be an ideal two-dimensional catalytic support due to its excellent electrical and thermal conductivity, mechanical strength, large surface area and incredibly high mobility of charge carriers. Lately, continuous efforts have been exerted to further improve the graphene textural and electronic properties by loading an optimum content of TiO2 for high efficiency solar-based application. In this review paper, an introduction of graphene / TiO2-graphene film, mechanism of formation, synthesis method, and potential solar applications are reviewed in details.
Keywords: Graphene